Immunohistochemical and Ultrastructural Imaging of the SARS-CoV-2 Coronavirus in Lung, Lymph Node, and Kidney Tissues of Deceased Patients - A. A. Odilov; A. V. Volkov; A. O. Abdullaev; A. K. Shadmanov; A. B. Sudarikov; I. I. Babichenko (Туберкулез и болезни лёгких)
The objective: immunohistochemical and electron microscopic imaging of the SARS-CoV-2 coronavirus in lung, lymph nodes and kidney tissues of patients who died of COVID-19.Subjects and Methods. For immunohistochemical tests, specimens of sections of formalin-fixed and paraffin-embedded tissues of the lungs, lymph nodes and kidneys of patients who died from COVID-19 were used. Quantitative assessment of the SARS-CoV-2 viral load level was carried by the original RT qPCR and calculated by the formula: SARS-CoV-2 copy number/ABL1 х 100 copies, expressed as the ratio of the true number of SARS-CoV-2 cDNA copies per 100 copies cDNA of the ABL1 gene. For morphological tests, samples of native lung, lymph node and kidney tissues were taken.Results. Immunohistochemical and electron microscopic tests revealed particles of the SARS-CoV-2 coronavirus in the cytoplasm of endothelial cells of air-blood barrier of the lungs, the vascular glomerulus of the kidneys, in the cytoplasm of macrophages of the lymph node, and also in cytoplasm of lymphocytes in the lumen of lung capillaries.